Effect of Dentin Surface Treatment Using a Non-Thermal Argon Plasma Brush on the Bond Strength of a Self-Adhesive Resin Composite - Aida Moradi (Islamic Dental Association of Iran, 2019)
Background and Aim: Improving the bond strength at the resin-dentin interface is an important challenge in adhesive dentistry. This study examined the effect of low-power, non-thermal atmospheric pressure plasma (NT-APP) treatments on the adhesion of a self-adhesive resin composite to dentin. Materials and Methods: In this experimental in-vitro study, buccal enamel of extracted bovine incisors was removed using a high-speed diamond bur. The specimens were randomly divided into two groups according to the plasma treatment and thermocy-cling. The non-thermal atmospheric argon plasma brush was used in this study. One subgroup was subjected to the microshear bond strength (µSBS) test after 24 hours, whereas the other subgroup was subjected to artificial aging with thermocycling for 5000 cycles before being tested. Each specimen was attached to a testing jig and loaded at a crosshead speed of 1.0 mm/minute in a universal testing machine until failure occurred. Data were analyzed using two-factor repeated measures analysis of variance (ANOVA). Results: The results of μSBS testing showed that with plasma treatment, the average μSBS increased to 34.20±12.12 MPa compared to 19.47±7.4 MPa in the controls (P=0.002). After 5000 cycles of thermocycling, the adhesive-dentin bonding strengths of the plasma-treated specimens slightly decreased from 34.20±12.12 MPa to 33.64±5.6 MPa (P=0.886), while the strengths of the untreated specimens reduced from 19.47±7.4 MPa to 19.10±5.1 MPa (P=0.461). Plasma treatment improved the µSBS compared to the control group. After thermocycling, the µSBS did not decrease in the plasma and control (non-plasma) groups. Conclusion: Plasma treatment using NT-APP improves the adhesion of self-adhesive flowable resin composites to dentin.